Moderating Effect of Government Policies on the Relationship between Mobile Technology Services and Performance of Deposit-Taking Saccos in Kenya - Mugo, David M.; Waithaka, Stephen T.; Muathe, Stephen (IJSET, 2017)
The study sought to determine the moderating effect of government policies on the relationship between mobile technology services and performance of Deposit-Taking Savings and Credit Cooperative Societies (SACCOs) in Kenya. Descriptive and explanatory research designs were adopted based on a sample of 86 Deposit-Taking SACCOs. A structured questionnaire administered to two managers in each SACCO was used for data collection. The study found that government policies positively moderates the relationship between mobile technology services and performance of Deposit-Taking SACCOs implying that appropriate government policies that are favourable for the Deposit- Taking SACCOs should be formulated.
Keywords: Deposit-Taking SACCO; Mobile Technology Services; Government Policies